PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPATU CASUAL MEREK BATA - HANNA MEILANI DAMANIK (JURNAL ILMIAH KOHESI, 2018)
Higher demand for shoe products indicates that the shoe market in Indonesia is very promising. One brand of shoes that sells its products in Indonesia is Bata. Consumer decision to make purchases is influenced by product quality and price. The sample used is 40 respondents. The result of this research shows that Bata casual shoe purchasing decision is influenced by consumer perception about the price offered by Bata shoes. The quality of the product in this study did not give a significant effect on the purchase decision of Bata casual shoes.